Trapped by scandal [large type] - Feather, Jane (Thorndike Press, 2016)
Lady Hero Fanshawe has chafed at society's dictates since the death of her fiancé taught her that joy can be fleeting. When her brother disappears in Paris at the height of the Terror, she has no hesitation in disguising herself as a boy and risking her life to find him--or in joining forces with a chance-met ally, the enigmatic William Ducasse, Viscount St. Aubrey. And she has no regrets in indulging in a passionate affair with the dangerously handsome stranger, in the shadow of the guillotine...Half French, half English, William is committed to his shadow life, flirting with death to rescue imperiled aristocrats. Marriage is an indulgence he cannot afford. Once Hero returns to London, he refuses to risk her good name by continuing their liaison. But he has reckoned without the determined Hero's disregard for propriety...or the dictates of his own heart. --Amazon.com